The Effect of Transformational Leadership on Firm Performance through ERP Systems and Supply Chain Integration in the Food and Beverage Industry - Kezia Jade Setiabudi; Hotlan Siagian; Zeplin Jiwa Husada Tarigan (Master of Management, School of Business and Management, Petra Christian University, 2021)
This study aims to examine the effect of transformational leadership on company performance using ERP technology and supply chain integration in food and beverage companies. The survey uses a questionnaire designed using a 5-point Likert scale. As many as 100 questionnaires were distributed to 100 food and beverage companies domiciled in the region of Surabaya, East Java, Indonesia. Respondents were from the supervisor and upper level as considered the most knowledgeable person in the company. The number of valid data is 55 respondents representing 55 companies from 100 respondents. Data analysis using Smart PLS. The results of the data analysis show that transformation Leadership does not directly affect firm performance; transformation Leadership does not affect supply chain integration. ERP Application influences firm Performance, supply chain integration influences firm performance, ERP Application affects supply chain integration. An additional finding is that transformational leadership indirectly affects firm performance. This result enriches the insight for the manager in enhancing firm performance. This paper also contributes to the current research in the field of supply chain management.